Motivation of mentally superior Filipino children and its correlates - Zotomayor, Perla A. (Perla Ambrosio) 1948- (Quezon City College of Education, University of the Philippines Diliman, 1987)
The purpose of the study is to determine the motivation of mentally superior Filipino children in the intermediate level, using a researcher-designed instrument. A comparison of the motivation of mentally superior children with that of the average children is done. Mentally superior children's motivation is also correlated with their mental abilities, aspirations, and school achievement. The study further determines the differences in motivation among the respondents who are grouped according to: type of school, sex, employment of parents, educational attainment of parents, number of children in the family, and birth order.
Thesis (Master of Education)--University of the Philippines, Diliman
Typescript.
Vita.
Keywords: Gifted children -- Education -- Philippines; Motivation (Psychology).